2021
DOI: 10.1007/s00115-020-01056-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychische Belastung während der COVID-19-Pandemie: Konsequenzen für psychiatrisch Erkrankte und therapeutische Implikationen

Abstract: Zusammenfassung Hintergrund Der Ausbruch der COVID-19-Erkrankung und die rasche Ausbreitung des sie verursachenden Coronavirus SARS-CoV‑2 bedroht weltweit nicht nur die physische, sondern auch die psychische Gesundheit der Bevölkerung. Seine Auswirkungen auf Neuerkrankungen und die Entwicklung bestehender Erkrankungen im ambulanten psychiatrischen Bereich in Deutschland ist noch nicht untersucht. Methoden Die Dokumentation in den Akten von 68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 37 publications
1
10
1
5
Order By: Relevance
“…The present study shows that medical care and its limitations are decisively linked to the health status of the people with mental disorders. This illustrates the importance of providing secure medical care and is in line with the conclusions of Winkler et al [ 46 ], who emphasize the importance of therapeutic offers (as far as hygiene regulations and contact restrictions allow) and active contact with people with mental disorders during pandemic restrictions.…”
Section: Discussionsupporting
confidence: 86%
“…The present study shows that medical care and its limitations are decisively linked to the health status of the people with mental disorders. This illustrates the importance of providing secure medical care and is in line with the conclusions of Winkler et al [ 46 ], who emphasize the importance of therapeutic offers (as far as hygiene regulations and contact restrictions allow) and active contact with people with mental disorders during pandemic restrictions.…”
Section: Discussionsupporting
confidence: 86%
“…Another study found a generally low level of knowledge of COVID-19, lower compliance with health regulations and a lower level of anxiety regarding COVID-19 in comparison to the general population (4). Attempts to test the differential impact of the pandemic suggest that people with affective disorders are far more affected by the restrictions imposed by COVID-19, whereas people with psychotic disorders are less affected (5,6) Specific population groups may be especially vulnerable to stress resulting from the COVID-19 crisis. Psychiatric patients have more precarious employment (7); smaller social networks (8); lower health literacy (9); greater physical vulnerability via higher rates of obesity (10), and smoking (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Allgemein Dass Menschen mit einer Vorgeschichte von psychischen Problemen im Kontext der Corona-Pandemie eine besonders vulnerable Gruppe darstellen, ist vielfach betont worden [39,117]. Im Klientel einer deutschen Institutsambulanz fand man bei 60 % der dort behandelten Patienten Belastungen durch die COVID-19 Krise, wobei die Angst vor einer Infektion weniger häufig war als die Belastung durch die Schutzmaßnahmen [118]. Es geht aber nicht nur um eine potentielle Verschlechterung der Symptomatik und/oder der Behandlung der psychischen Erkrankungen, es ist auch das Risiko für das Auftreten einer Infektion erhöht, ebenso findet man häufiger schwerere Verläufe und eine erhöhte Mortalität.…”
Section: Menschen Mit Psychischen Erkrankungen Als Besonders Vulnerable Risikogruppeunclassified